The Comprehensive Management of Diabetes Mellitus: A Literature Review - Abidzah, Rendy Zayyan; Wardhani, Fitria Kusuma (Journal of Diverse Medical Research : Medicosphere, 2024)
ABSTRACTBackground: The number of people with diabetes mellitus (DM) increased from 108 million in 1980 to 422 million in 2014. Prevalence is increasing faster in low- and middle-income countries than in high-income countries. The rapid increase in the number of people with diabetes is a global crisis that places a huge burden on public health systems.1Methods. Literature searching was conducted using databases such as PubMed, Google Scholar, and Web of Science using Search terms included "diabetes," "management," "carbohydrate,". Systematic reviews of peer-reviewed articles, reports, and case studies were chosen.Conclusion: The proper management of diabetes mellitus is important to eliminate symptoms and improve the patient’s quality of life. Key words: diabetes mellitus, carbohydrate, management